2015
DOI: 10.1093/cid/civ363
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline Leads to Sterility and Enhanced Killing of FemaleOnchocerca volvulusWorms in an Area With Persistent Microfilaridermia After Repeated Ivermectin Treatment: A Randomized, Placebo-Controlled, Double-Blind Trial

Abstract: Sub-optimal responses to ivermectin (IVM) have emerged. Targeting the Onchocerca volvulus Wolbachia endosymbionts with doxycycline is effective in clearing microfilariae in onchocerciasis patients with persistent microfilaridermia and in enhanced killing of adult worms after repeated standard IVM treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 31 publications
4
57
0
Order By: Relevance
“…65% of the female worms in the control group (ALB 3d) were Wolbachia -positive (Table 2), a level that is consistent with other endemic areas with lowered transmission and a higher proportion of older worms [10], possibly induced by MDA or as a result of intensified gold digging and thus pollution of the water breeding habitat of the vector [38]. In contrast, only 1.3% contained intact Wolbachia in the standard treatment group (DOX 4w).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…65% of the female worms in the control group (ALB 3d) were Wolbachia -positive (Table 2), a level that is consistent with other endemic areas with lowered transmission and a higher proportion of older worms [10], possibly induced by MDA or as a result of intensified gold digging and thus pollution of the water breeding habitat of the vector [38]. In contrast, only 1.3% contained intact Wolbachia in the standard treatment group (DOX 4w).…”
Section: Resultssupporting
confidence: 78%
“…The number and type of AR were similar in the DOX 4w and DOX 3w group, therefore a longer treatment time does not alter AR. It is important to note that the range of AR after DOX is similar to that seen in a previous study [10], in which DOX was used in lower doses and was performed under blinded conditions. MIN associated AR were mainly dizziness, a common side effect of this drug.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Numerous clinical studies in onchocerciasis (or LF) have been conducted to examine the effect of different dose regimens of doxycycline, rifampicin and azithromycin (Hoerauf et al., 2001, Hoerauf et al., 2003, Debrah et al., 2006, Richards et al., 2007, Specht et al., 2008, Hoerauf et al., 2008a, Hoerauf et al., 2009, Turner et al., 2010, Debrah et al., 2015, Abegunde et al., 2016). To date, doxycycline has shown the highest efficacy.…”
Section: Research For New Drugs For Onchocerciasis Control and Eliminmentioning
confidence: 99%
“…As an alternative approach, endosymbiotic Wolbachia bacteria present in most human pathogenic filariae, including those causing onchocerciasis and lymphatic filariasis, can be targeted with antibiotics [10][11][12]. In human clinical trials doxycycline and rifampicin treatment have been shown to deplete Wolbachia, leading to the sterilization of female adult filariae of Onchocerca volvulus and Wuchereria bancrofti as well as to adult worm death [12][13][14][15]. Moreover, since Loa loa filariae do not possess endosymbiotic Wolbachia, drug-related serious adverse events in areas co-endemic for loiasis are unlikely to occur with Wolbachia-targeting drugs [9,16].…”
Section: Introductionmentioning
confidence: 99%